67. Cortical evoked potentials after stimulation of cutaneous nerve fibres by micro-patterned electrodes with different interrail gaps. Issue 12 (December 2017) - Marinelli, L.; Pellegrino, L.; Leandri, M.
Abstract : To demonstrate that selective stimulation of intraepidermal nociceptive free endings can be performed using a micro-patterned comblike electrode with interrail gap of 150 μm. In 5 healthy subjects, we stimulated the skin of the hand dorsum with the micro-patterned electrode and with a similar electrode with interrail distance of 1 mm. Stimulation was performed with bursts of 10 pulses, 0.2 ms width each, period of 1 ms either delivered randomly or with constant rate. Cortical responses were recorded from Cz-Au and C3′/C4′-Fz. Stimulating with 1 mm electrode C3′/C4′ recordings showed N20 and W shaped SEP complex; Cz-Au derivation produced a smaller W complex and later smaller N1-P1 waves. Stimulating with 150 μm electrode C3′/C4′ recordings showed only the N1-P1 complex, while no early or medium-latency responses were visible; the Cz-Au recordings showed the N2-P2 complex. The 1 mm gap electrode stimulated large afferents, responsible of the medium-latency components of SEP W. Such components could not be detected with the 150 μm, indicating that large afferents were not stimulated and only small fibre nociceptive afferents were responsible for the late components. The micro-patterned electrode can be considered selective for nociceptive afferents.